STRUCTURE AND CONTENT OF TEACHER COMPETENCIES - Šteinberga, Airisa; Kazāke, Dace (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Significant changes in the society of the XXI century determine the changes in the education system. Nowadays the challenge of promoting child development is important. Teaching subjects does not give a generalised idea about nature, society and people in general. Teachers need new competences to move to logic of human development in education. The article analyses teacher’s communicative, self-cognition and cognitive management, methodological and organisational function that are united and contribute to the balanced development of pupils, therefore, in accordance with these functions, it is necessary to acquire the corresponding competences. By analysing theoretical literature, the article reveals the structure and content of these competencies.